Business to Business Marketing in Bhutan: A Case Study from Balam Gewog under Mongar Dzongkhag - Pema, Kinley; Dendup, Tashi; Chhetri, Rekha (Bhutan Journal of Natural Resources and Development, 2020)
The Commercial Agriculture and Resilient Livelihoods Enhancement Programme (CARLEP) and the Regional Agricultural and Marketing Cooperative (RAMCO) piloted the business to business (B2B) marketing model in 2018 to address smallholder farmers’ marketing issues in Eastern Bhutan. As the B2B pilot model is currently not functional, it is vital to understand the B2B model’s challenges to successfully replicate the interventions in other communities. The lack of follow-up studies on the B2B marketing model motivated the authors to investigate the model’s challenges for implementation in the country. This case study was based on six vegetable groups in Balam Gewog, Mongar, Bhutan. Primary data were collected through focus group discussions with six vegetable groups and in-depth interviews with key informants. Secondary data were collected from Gewog, CARLEP, and RAMCO. The results showed that the B2B marketing model adopted in Balam Gewog was a primary B2B marketing model – a linkage only for selling produce. Four critical issues with the B2B marketing model adopted in Balam Gewog were noted: (1) mismatch between vegetable production and collection schedule, (2) lack of quantity and quality specification of vegetables in the contract between vegetable farmers’ groups and the buyer, (3) inadequate support services, and (4) lack of monitoring by facilitating organisations after contract signing between vegetable farmers’ groups and the buyer. Accordingly, we recommend adjusting the collection schedule as per the production season, specifying contract clauses like quantity and quality of produce, improving support services, and monitoring business by relevant authorities.